Onsite infectious agents and toxins monitoring in 12 May Sichuan earthquake affected areas - Yao, Maosheng; Zhu, Tong; Li, Kejun; Dong, Shuofei; Wu, Yan; Xinghua Qiu; Jiang, Bo; Chen, Liansheng; Zhen, Shiqi (Journal of Environmental Monitoring, 2009)
At 14: 28 on 12 May 2008, Sichuan Province of China suffered a devastating earthquake measuring 8.0 on the Richter scale with more than 80 000 human lives lost and millions displaced. With inadequate shelter, poor access to health services, and disrupted ecology, the survivors were at enormous risk of infectious disease outbreaks. This work, believed to be unprecedented, was carried out to contain a possible outbreak through onsite monitoring of airborne biological agents in the high-risk areas. In such a mission, a mobile laboratory was developed using a customized vehicle along with state-of-art bioaerosol and molecular equipment and tools, and deployed to Sichuan 11 days after the earthquake. Using a high volume bioaerosol sampler (RCS High Flow) and Button Inhalable Aerosol Sampler equipped with gelatin filters, a total of 55 air samples, among which are 28 filter samples, were collected from rubble, medical centers, and camps of refugees, troops and rescue workers between 23 May and 9 June, 2008. After pre-treatment of the air samples, quantitative polymerase chain reaction (qPCR), gel electrophoresis, limulus amebocyte lysate (LAL) assay and enzyme-linked immunosorbent assay (ELISA) were applied to detect infectious agents and to quantify environmental toxins and allergens. The results revealed that, while high levels of endotoxin (180 similar to 975 ng/m(3)) and (1,3)-beta-D-glucans (11 similar to 100 ng/m(3)) were observed, infectious agents such as Bacillus anthracis, Bordetella pertussis, Neisseria meningitidis, Mycobacterium tuberculosis, influenza A virus, bird flu virus (H5N1), enteric viruses, and Meningococcal meningitis were found below their detection limits. The total bacterial concentrations were found to range from 250 to 2.5 x 10(5) DNA copies/L. Aspergillus fumigatus (Asp f 1) and dust mite allergens (Der p 1 and Der f 1) were also found below their detection limits.